2018
DOI: 10.1093/ije/dyx279
|View full text |Cite
|
Sign up to set email alerts
|

Burden of hypertension in The Gambia: evidence from a national World Health Organization (WHO) STEP survey

Abstract: Rural and semi-urban residence were strongly associated with hypertension, contrary to what has been found in similar studies in sub-Saharan Africa. Intervention to reduce the burden of hypertension in The Gambia could be further targeted towards rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 43 publications
(45 reference statements)
5
56
0
1
Order By: Relevance
“…For instance, the prevalence was below 20% in some surveys [ 25 27 ] while some studies showed prevalence about 25%, close to that seen in our study [ 28 30 ]. In other studies, prevalence was much higher, above 30% [ 31 ]. The findings indicate significant differences in the prevalence due to various reasons and hence there is a need to conduct a meta-analysis to summarize these data.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, the prevalence was below 20% in some surveys [ 25 27 ] while some studies showed prevalence about 25%, close to that seen in our study [ 28 30 ]. In other studies, prevalence was much higher, above 30% [ 31 ]. The findings indicate significant differences in the prevalence due to various reasons and hence there is a need to conduct a meta-analysis to summarize these data.…”
Section: Discussionmentioning
confidence: 93%
“…Four studies assessed prevalence of obesity [18][19][20][21] and three of those studies reported on the overall prevalence [18][19][20], ranging from 2.3% [19] to 11.7% [18]. Three studies distinguished between males and females [18,20,21]. All of those studies showed a significantly higher prevalence of overweight and obesity in females than in males.…”
Section: Prevalence Of Cardiovascular Disease Risk Factorsmentioning
confidence: 99%
“…Three studies that distinguished between different age groups found that prevalence increases with age [18,22,23]. Cham et al assessed the prevalence of undiagnosed hypertension and found that 79% of participants were unaware of their condition before the survey [18]. Prevalence of unawareness was higher in males than in females and in the younger age groups [18].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertension is a common chronic disease which is mainly characterized as continuous increase of arterial blood pressure. Hypertension has become the most familiar "epidemic disease" in the world [1], which has caused great economic and social burden [2]. Hypertension often leads to dysfunction of kidney [3], brain [4], heart [5] and other important organs.…”
Section: Introductionmentioning
confidence: 99%